2022
DOI: 10.1080/21645515.2022.2069427
|View full text |Cite
|
Sign up to set email alerts
|

Measuring parents’ acceptance of non-national immunization program vaccines for children and its influencing factors during the COVID-19 pandemic in Shanghai, China

Abstract: This study aimed to understand the willingness of and affecting factors of non-national immunization program (non-NIP) vaccines among children’s parents during the COVID-19 era in Shanghai, China. A cross-sectional survey was conducted with parents who attended vaccination clinics in four out of 16 districts in Shanghai, China. Data was obtained using a self-administered structured questionnaire. A multivariate logistic regression model was used to analyze factors associated with vaccination acceptability. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 17 publications
0
8
1
Order By: Relevance
“…Characteristics between participants and refusals could not be compared as no information was collected from refusals. Nonetheless, our response rate in both rounds was higher than in studies with similar topics [ 29 , 30 , 31 , 34 , 37 , 38 , 40 , 41 , 49 ]. Last but not least, the study was cross-sectional and so it could not establish causal relationships.…”
Section: Discussioncontrasting
confidence: 82%
See 2 more Smart Citations
“…Characteristics between participants and refusals could not be compared as no information was collected from refusals. Nonetheless, our response rate in both rounds was higher than in studies with similar topics [ 29 , 30 , 31 , 34 , 37 , 38 , 40 , 41 , 49 ]. Last but not least, the study was cross-sectional and so it could not establish causal relationships.…”
Section: Discussioncontrasting
confidence: 82%
“…The levels of parental acceptability in both rounds were higher than that reported in the United States (39.7%) [ 26 ] and the United Kingdom (48.2%) [ 27 ]. However, such levels of parental acceptability among our participants were lower when compared to Chinese parents having older children [ 31 , 33 , 34 , 37 , 38 , 40 , 49 ]. Younger age of the children and the availability of vaccines might be reasons to explain such differences.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Lack of national financing also contributed to a relatively higher market cost of vaccination, especially for the payers (caregivers of children). This higher cost of non-NIP vaccination might be closely connected to the hesitation observed in public health workers who “used to recommend but not accepted”, as the cost often exceeds the caregivers’ willingness to pay for non-NIP vaccines [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…A survey conducted in Shanghai, China revealed that factors such as income, education and convenience influence the acceptability of non-NIP vaccines. The survey also found that half of the participants who would not have opted for non-NIP vaccines would change their decision if non-NIP vaccines were covered by health insurance 17. The largest factor contributing to inequality in non-NIP vaccines is monthly household income per capita 6.…”
Section: Towards Efficient and Fair Pricingmentioning
confidence: 99%